A NEED ANALYSIS ON ICT-BASED ENGLISH MATERIAL FOR TEACHING AND LEARNING OF READING FOR HIGH SCHOOL STUDENTS IN SOUTH BENGKULU - Margareta Margareta; Safnil Safnil; Irwan Koto (JOALL (Journal of Applied Linguistics and Literature), 2017)
This research was aimed to find out ICT media are preferred by high school students in South Bengkulu in learning reading and to describe the reading materials should be used with ICT media. The research design was mixed method quantitative and qualitative with the subjects of this research were 302 high school students and 11 English teachers in South Bengkulu. The instruments of this research were questionairre and open-ended interview. The findings of the research revealed that (1) online ICT media was prefered  by high school students in South Bengkulu in learning reading  and (2)  kinds of text became the reading material that should be used with ICT media. To suggest, a broader field test still needed to be done to achieve a better result and other researchers who are interested in the incorporation of ICT in learning teaching are suggested to conduct further investigation which possibly deals with other language skills.